Explainable, transparent autonomous agents and multi-agent systems : second International Workshop, EXTRAAMAS 2020, Auckland, New Zealand, May 9-13, 2020, Revised selected papers /: second International Workshop, EXTRAAMAS 2020, Auckland, New Zealand, May 9-13, 2020, Revised selected papers. (2020) - Unknown
No abstract available